Male biased gene flow in banana pseudostem weevil (Odoiporus longicollis Oliver) as revealed by analysis of the COI-tRNA(Leu) COII region - Shankar, Pallavi; Kulkarni, Vishvas M.; Kumar, Lalitha Sunil (Genetica, 2015)
The genetic diversity amongst thirty weevils representing six Indian populations of banana pseudostem weevil i.e. Odoiporus longicollis (Oliver) was estimated by sequence analysis of the partial COI-tRNA(Leu)-COII region. The sequences exhibited AT bias typical of insect mitochondrial DNA which was highest in the first codon position of COI and in the third codon position of COII. There was no phylogeographic distribution of the populations. The Fu and Li's D and F tests were non-significant for this mitochondrial region. No Wolbachia infection was detected in any of the populations. The genetic differentiation amongst the populations was highly significant (p < 0.001; chi(2) = 123.333; df = 75), suggesting restricted gene flow between the populations. This result did not correlate with that obtained with nuclear rDNA markers i.e. ITS1 and ITS2, suggesting a male biased gene flow between the populations.
Keywords: Banana pseudostem weevil; COI-tRNA(Leu) -COII; Genetic differentiation; Male biased gene flow; Odoiporus longicollis (Oliver)

Analyses of the internal transcribed rDNA spacers (ITS1 and ITS2) of Indian weevils of Odoiporus longicollis (Olivier) reveal gene flow between locations - Kumar, Lalitha Sunil; Shankar, Pallavi; Kulkarni, Vishvas M. (International Journal Of Tropical Insect Science, 2018)
An important step towards developing a successful integrated pest management (IPM) programme for the control of banana pseudostem weevil, Odoiporus longicollis (Olivier), a serious pest of banana in India, is the study of the population structure of the pest. In the present study, the genetic variation among 30 individual weevils of O. longicollis collected from six different locations was assessed by analysing the primary nucleotide sequences of the rDNA ITS1 and ITS2 regions. AMOVA, Mantel test, and the maximum likelihood trees of the haplotypes failed to reveal any phylogeographic structuring, which was confirmed by haplotype analysis and genetic differentiation estimates. The results indicate that the locations are not differentiated, i.e. there is gene flow between the locations. The star-shaped networks revealed a signature of demographic expansion that was confirmed by the different demographic tests. These results provide important information, which is essential for the development of suitable strategies for the control of this banana pest, as well as management of its resistance to insecticides.